Correlative Imaging in a Patient with Cystic Thymoma: CT, MR and PET/CT Comparison - Romeo, Valeria (Pol J Radiol, 2015)
BACKGROUND: Cystic thymoma is a rare variant of thymic neoplasm characterized by almost complete cystic degeneration with mixed internal structure. We describe a case of a 60 year-old woman with a cystic thymoma studied with advanced tomographic imaging stydies. CT, MRI and PET/CT with (18)F-FDG were performed; volumetric CT and MRI images provided better anatomic evaluation for pre-operative assessment, while PET/CT was helpful for lesion characterization based on (18)F-FDG uptake. Although imaging studies are mandatory for pre-operative evaluation of cystic thymoma, final diagnosis still remains surgical. CASE REPORT: A 60-year-old woman with recent chest pain and no history of previous disease was admitted to our departement to investigate the result of a previous chest X-ray that showed bilateral mediastinal enlargement; for this purpose, enhanced chest CT scan was performed using a 64-rows scanner (Toshiba, Aquilion 64, Japan) before and after intravenous bolus administration of iodinated non ionic contrast agent; CT images demonstrated the presence of a large mediastinal mass (11×8 cm) located in the anterior mediastinum who extended from the anonymous vein to the cardio-phrenic space, compressing the left atrium and causing medium lobe atelectasis; bilateral pleural effusion was also present. CONCLUSIONS: In conclusion, correlative imaging plays a foundamental role for the diagnostic evaluation of patient with cystic thymoma. In particular, volumetric CT and MRI studies can provide better anatomic informations regarding internal structure and local tumor spread for pre-operative assessment. Conversely, metabolic imaging using (18)F-FDG PET/CT is helpful for lesion characterization differentiating benign from malignant lesion on the basis of intense tracer uptake. The role of PET/MRI is still under investigation. However, final diagnosis still remains surgical even though imaging studies are mandatory for pre-operative patient management.